Volt: A Lazy Grounding Framework for Solving Very Large MaxSAT Instances - Mangal, Ravi; Zhang, Xin; Naik, Mayur; Nori, Aditya (SAT '15: International Conference on Theory and Applications of Satisfiability Testing, 2015)
Very large MaxSAT instances, comprising 1020 clauses and beyond, commonly arise in a variety of domains. We present VOLT, a framework for solving such instances, using an iterative, lazy grounding approach. In each iteration, VOLT grounds a subset of clauses in the MaxSAT problem, and solves it using an oﬀ-the-shelf MaxSAT solver. VOLT provides a common ground to compare and contrast diﬀerent lazy grounding approaches for solving large MaxSAT instances. We cast four diverse approaches from the literature on information retrieval and program analysis as instances of VOLT. We have implemented VOLT and evaluate its performance under diﬀerent state-of-the-art MaxSAT solvers.